1983
DOI: 10.1093/oxfordjournals.aje.a113680
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Markers in Italy

Abstract: Among 5005 Navy recruits aged 18-26 years from all sections of Italy, whose blood was tested in 1981, regional prevalence of serologic markers for hepatitis B was higher in southern Italy and in the Italian islands as compared with northern Italy and central Italy (4.3% vs. 2.3% for hepatitis B surface antigen (HBsAg) and 23.5% vs. 10.5% for any B marker). Social-demographic variables such as region, family size, and education were associated with hepatitis B as were the more traditionally associated variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 0 publications
1
21
0
3
Order By: Relevance
“…Other countries (8)(9)(10)(11)(12) have also reported geographical variations of HBsAg seropositivity within their countries. Among them, the study from China (8) showed a higher positivity of HBsAg in coast areas, comparable with ones from Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Other countries (8)(9)(10)(11)(12) have also reported geographical variations of HBsAg seropositivity within their countries. Among them, the study from China (8) showed a higher positivity of HBsAg in coast areas, comparable with ones from Korea.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed only a few risk factors for low vaccine coverage and for acquiring chronic HBV infection. Other important factors such as low socioeconomic status and household crowding were not assessed [29][30][31][32][33]. Additionally, small numbers of HBsAg positive children limited stratification by receiving a birth dose and limited evaluation of the impact of ≥3 dose hepatitis B coverage.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in HBV, HDV and HCV endemicity in Italy has been shown in the past 2 decades, [29][30][31][32] but the present epidemiologic conditions still call for studies on multiple hepatitis infections.…”
Section: Discussionmentioning
confidence: 99%